(untitled) (Revista Argentina de Musicología, 2022)
Since the beginning of the 20th century we have witnessed the vertiginous advance of sound recording, processing and reproduction technologies. Likewise, phonographic production practices have been modified, moving away from the documentary conception of analog recording and reproduction media, whose impact on recorded sound sought to make itself invisible behind rhetoric of transparency. This is mainly due to the impact that the operations carried out by sound engineers and technicians have on sound, both during recording and post-production. On the other hand, the advent of digital technologies dedicated to phonographic production, parallel to the creation towards the end of the 20th century of the world wide web and the exchange of information it enabled, led not only to an unprecedented dispersion of specific technology for musical creation, but also to the proliferation of creative uses not initially foreseen in its design. In fact, many of them quickly crystallized into practices that gave rise to unique phonographic effects, also erected as characteristic features of various musical styles. However, it happens that the accumulation of practices, both standardized and creative, may eventually collide with assumptions about the authenticity of a phonographic record, and about the limit at which a specific phonographic practice can constitute a hoax. In this sense, the objective of this paper is to observe and describe the different modes of use of the pitch correction technology popularly known as autotune in the live version of the song "Goteo", belonging to Duki, an argentine trap artist. The following hypotheses guide our work: first, to affirm that the implementation of autotune is essential for the sound design of the musical person. Second, to maintain that its implementation responds to both a corrective and an artistic-creative decision.